Characteristics and Welfare of Long-Term Shelter Dogs - Christina Raudies; Susanne Waiblinger; Christine Arhant (Animals, 2021)
To identify characteristics that distinguish long-term (LT: stay > 1 year) from short-term shelter dogs (ST: ≤5 months) and to investigate if a long-term stay impairs welfare, we compared ST and LT dogs in Austrian no-kill shelters. Analyses including characteristics such as breed, sex, or age (shelter records), problem behaviour, and personality (questionnaires completed by staff) showed that LT dogs were significantly more often a “dangerous breed”, male, and older when admitted to the shelter. They were rated higher on “aggression” and “high arousal” and lower on the personality dimension “amicability”. A welfare assessment protocol including reaction toward humans (Shelter Quality Protocol), and in-kennel observations were used to assess the effect of the long-term stay. LT dogs tended to show more signs of aggression toward an unfamiliar human, but welfare assessment revealed no difference. During resting periods, LT dogs spent more time resting head up and had more bouts resting head down. Prior to feeding, they stood, vocalised, and yawned more. LT dogs are characterised by specific features such as being aroused easily and having difficulties to relax. Whether this is a result of the long-term stay or personality-associated, consequently causing lower adoption rates, remains to be determined.